Essential newborn care practices in health facilities of Nepal: Evidence from Nepal Health Facility Survey 2015 and 2021. - Achyut Raj Pandey; Bikram Adhikari; Bipul Lamichhane; Bishnu Dulal; Saugat Pratap K C; Deepak Joshi; Sushil Chandra Baral (Public Library of Science (PLoS), 2024)
Availability of newborn care practices in health facilities (HFs) plays an important role in improving the survival and well-being of newborns. In this paper, we aimed to assess practice of carrying out different newborn care practices among HFs between 2015 and 2021, and associated factors in Nepal. We analyzed data of 621 and 786 HFs offering delivery and newborn care services from Nepal Health Facility Surveys 2015 and 2021, respectively. We summarized categorical variables with a weighted percent and 95% confidence interval (CI). We estimated weighted unadjusted absolute difference in percentage of different newborn care practices between 2015 and 2021, and its 95% CI using binomial regression model. We applied univariable and multivariable logistic regression analysis to determine the factors associated with the availability of all seven newborn care practices. The percentage of HFs carrying out all seven newborn care practices was 50.5% (95% CI: 44.6, 56.3) in 2015 and 83.7% (95% CI: 79.8, 87.0) in 2021 with an overall difference of 33.3 percent points (95% CI: 26.4, 40.1). The proportion of HFs reporting all seven newborn care practices increased significantly between 2015 and 2021 in each all three ecological regions and in provinces except Madhesh and Gandaki. In 2021, private hospitals had lower odds of carrying out all seven newborn care practices compared to federal/provincial hospitals (AOR = 0.26, 95% CI: 0.11, 0.63). Similarly, in 2021, the odds of HFs carrying out all seven newborn care practices was 2.87 (95% CI: 1.06, 8.31) times higher in Sudurpashchim compared to Koshi province. In 2021, HFs carrying out seven newborn care practices did not differ significantly based on ecological belts, quality assurance activities, external supervision, delivery service-related training, and frequency of HF meetings. In conclusion, there has been significant improvement in proportion of facilities carrying out seven essential newborn care practices between 2015 and 2021. Type of facility and provinces were associated with the HFs carrying out seven newborn care practices in Nepal.